2009
DOI: 10.1002/mawe.200900531
|View full text |Cite
|
Sign up to set email alerts
|

Processing and characterization of a cobalt based alloy for use in diamond cutting tools

Abstract: Most of the alloys used as bonding matrix in diamond tools show a high content of cobalt -which is undesirable due to a series of reasons. In the last decade, some attempts were made towards the reduction of the Co content in these alloys. NEXT100J alloy (50wt%Cu-25wt%Fe-25wt%Co) by Eurotungstene is an example of it.This study aims to characterize the structure, microstructure and some mechanical properties of the NEXT100 -this is an comercial alloy widely used as bonding matrix for diamonds in cutting tools, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Prediction error was 11.7%, so the prediction results were good (Jang et al, 2014). The predication results show that the model has good precision (Oliveira et al, 2009). The predicted value of surface roughness under processing technology parameters (diamond abrasive grain, lateral pressure and reciprocating frequency of wire saw) can be obtained by using the limited test data through the model.…”
Section: Establishment and Prediction Of Surface Roughness Bp Modelmentioning
confidence: 88%
“…Prediction error was 11.7%, so the prediction results were good (Jang et al, 2014). The predication results show that the model has good precision (Oliveira et al, 2009). The predicted value of surface roughness under processing technology parameters (diamond abrasive grain, lateral pressure and reciprocating frequency of wire saw) can be obtained by using the limited test data through the model.…”
Section: Establishment and Prediction Of Surface Roughness Bp Modelmentioning
confidence: 88%
“…Microstructural studies confirmed that for this sintered alloy, a FeCo solid solution is embedded into a Cu matrix. The Cu solubility is limited to about 2% at 800 °C [ 132 , 133 ]. A fairly good agreement has been achieved between the developed thermodynamic description and experimental data from XRD measurements and microstructure analysis found in the literature.…”
Section: Iron-based Materials As Solutions For Crm Substitution Inmentioning
confidence: 99%
“…The Fe–Co solid solution is essential for commercial matrices, which is responsible for good tool properties because it strengthens the alloy [ 133 ]. These matrices contain most commonly about 20% cobalt, which is still a high content, and therefore the research on total cobalt substitution continues.…”
Section: Iron-based Materials As Solutions For Crm Substitution Inmentioning
confidence: 99%
“…Therefore, it is difficult to obtain higher density and substrate strength when using commonly used cobalt-based hot pressed sintered metal adhesives in pressureless sintering [ 9 ]. In order to improve the strength and diamond-holding force of pressureless sintering diamond tools, the composition of a diamond substrate needs to be designed, such as Fe-Cu-Co [ 18 , 19 ]. Additionally, some sintering aids need to be added [ 20 ].…”
Section: Introductionmentioning
confidence: 99%